Sustained-Paced Finger Tapping: A Novel Approach to Measure Internal Sustained Attention - Petilli, Marco A.; Trisolini, Daniela C.; Daini, Roberta (Frontiers in Psychology, 2018)
Sustained attention impairment is a common aftermath of both developmental and acquired neurological disorders and it is a fundamental prerequisite for all cognitive functions. To date, all the sustained attention tasks rely heavily on selective attention to external stimuli. The interaction between selective and sustained attention represents a limit in the field of assessment and may mislead researchers or distort conclusions. The aim of the present perspective study was to propose a Sustained version of the Paced Finger Tapping test (S-PFT) as a novel approach to measure sustained attention that does not leverage external stimuli. Here, we administered S-PFT and other attentional tasks (visual sustained attention, visuospatial attention capacity, selective attention, and divided attention tasks) to 85 adolescents. Thus, we provide evidence suggesting that S-PFT is effective in causing performance decrement over time, an important trademark of sustained attention tasks. We also present descriptive statistics showing the relationship between S-PFT and the other attentional tasks. These analyses show that, unlike visual sustained attention tests, performances to our task of internal sustained attention were not correlated to measures of selective attention and visuospatial attention capacity. Our results suggest that S-PFT could represent a promising and alternative tool both for empirical research and clinical assessment of sustained attention.